Investigation of α-glucosidase inhibitory activity of tetracera scandens leaf using fourier transform infrared spectroscopy-based metabolomics - Siddiqui, Mohammad Jamshed Ahmad; Nokhala, Ahmad; Saleh, Mohammed S.M.; Ahmed, Qamar Uddin (Medknow, 2020)
Introduction: Tetracera scandens is a shrub that belongs to Dilleniaceae family. The leaves of this plant have medicinal values and traditionally been used in the treatment of diabetes mellitus in Malaysia. The conventional quality control analysis of medicinal plantsthat relies on the quantification of few major metabolites is considered time-consuming since it requires extensive sample preparation and neglects the possible impacts that the other metabolites could have on the activity. Objectives: This study was aimed to investigate the α-glucosidase inhibitory (AGI) potential of different ratios of water-methanol extracts of T. scandens leaves and to establish a predictive multivariate model that could be used for the quality evaluation of T. scandens leaf based on the Fourier transform infrared (FT-IR) spectra of its extracts. Materials and Methods: Different ratios of solvent (0%, 20%, 40%, 60%, 80% and 100% methanol in water) were used to prepare a total of 36 extracts. The AGI potential and the FT-IR fingerprint spectrum were acquired for each extract. Results: A four components OPLS model (1+3+0) with R2Y of 0.951 and Q2Y of 0.916 was established to describe the correlation between the fingerprint FT-IR spectra of different T. scandens extracts and their corresponding AGI activities. The carbonoxygen, carbon-halide single bonds, as well hydroxyl and carbonyl groups were identified to be positively correlated with the AGI activity. Conclusion: An OPLS model was successfully developed as a rapid quality evaluation method to predict the AGI activity of T. scandens leaves.